Deoxyribonucleic Acid Methylation and Gene Expression of PPARGC1A in Human Muscle Is Influenced by High-Fat Overfeeding in a Birth-Weight-Dependent Manner - Brøns, Charlotte; Jacobsen, Stine; Nilsson, Emma; Rönn, Tina; Jensen, Christine B.; Storgaard, Heidi; Poulsen, Pernille; Groop, Leif; Ling, Charlotte; Astrup, Arne; Vaag, Allan (The journal of clinical endocrinology and metabolism, 2010)
Context: Low birth weight (LBW) and unhealthy diets are risk factors of metabolic disease including type 2 diabetes (T2D). Genetic, nongenetic, and epigenetic data propose a role of the key metabolic regulator peroxisome proliferator-activated receptor γ, coactivator 1α (PPARGC1A) in the development of T2D. Objective: Our objective was to investigate gene expression and DNA methylation of PPARGC1A and coregulated oxidative phosphorylation (OXPHOS) genes in LBW and normal birth weight (NBW) subjects during control and high-fat diets. Design, Subjects, and Main Outcome Measures: Twenty young healthy men with LBW and 26 matched NBW controls were studied after 5 d high-fat overfeeding (+50% calories) and after a control diet in a randomized manner. Hyperinsulinemic-euglycemic clamps were performed and skeletal muscle biopsies excised. DNA methylation and gene expression were measured using bisulfite sequencing and quantitative real-time PCR, respectively. Results: When challenged with high-fat overfeeding, LBW subjects developed peripheral insulin resistance and reduced PPARGC1A and OXPHOS (P < 0.05) gene expression. PPARGC1A methylation was significantly higher in LBW subjects (P = 0.0002) during the control diet. However, PPARGC1A methylation increased in only NBW subjects after overfeeding in a reversible manner. DNA methylation of PPARGC1A did not correlate with mRNA expression. Conclusions: LBW subjects developed peripheral insulin resistance and decreased gene expression of PPARGC1A and OXPHOS genes when challenged with fat overfeeding. The extent to which our finding of a constitutively increased DNA methylation in the PPARGC1A promoter in LBW subjects may contribute needs to be determined. We provide the first experimental support in humans that DNA methylation induced by overfeeding is reversible.Experimental support is provided showing that DNA methylations induced by overfeeding are reversible in humans.